Clinicopathological study and outcomes of primary extranodal lymphoma - Nichapa Nanthakwang (2020)
© 2019, Page Press Publications. All rights reserved. Lymphoma can present with either lymphadenopathy or extranodal involvement. There are limited clinicopathological data pertaining to the occurrence of primary extranodal lymphoma (pENL) in Thailand. This was a retrospective study conducted at Chiang-Mai University Hospital from 2012 to 2016. Patients 18 years of age and over and with a diagnosis of pENL were enrolled onto study. Data related to clinical presentations, histology, stage, treatment and response were collected. There were 104 pENL patients with a median age of 63 years included. The most common presentation was gastrointestinal symptoms (41%), followed by ear, nose, and throat symptoms (35%). Diffuse large B-cell lymphoma (DLBCL) was the most common morphological subtype (60%), followed by marginal zone lymphoma (15%). The majority of patients presented with stage II disease (55%). The five-year overall survival rate was 71%. The factors associated with mortality were hemoglobin <7 g/dL, B-symptoms and LDH above upper normal limits. This study illustrated that lymphoma can present at various extranodal sites. Gastrointestinal symptoms were the most common presentations and DLBCL was the most common subtype of pENL.